STUDI LINGKUNGAN PENGENDAPAN MENGGUNAKAN DATA GEOFISIKA LOGGING DI PT. ADIMITRA BARATAMA NUSANTARA KALIMANTAN TIMUR - Tamarindi Rachman Putr, Galih Adenanthera; Supriyanto, Supriyanto; Lepong, Piter (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2020)
This research conducted at PT. Adimitra Baratama Nusantara which is located in the Balikpapan formation and based on the administrative map of PT. Adimitra Baratama Nusantara is located in Sanga-Sanga, Kutai Kartanegara Regency, East Kalimantan Province. This study uses logging geophysical data in the form of log gammaray and log density where in this logging analysis aims to determine the direction of the spread of the layer by using correlation and to determine the depositional environment at the study site. The results obtained in this study based on logging geophysical data is the correlation of the distribution layer to the northeast and the depositional environment contained is the lower delta plain depositional environment, this is because the characteristics of the lower delta plain depositional environment are thin coal and medium-sized sandstone. . The lower delta plain environment is affected by shallow water when the bay is filled with sediment.